A Rare Case of Grey Zone Lymphoma Successfully Treated with Brentuximab Vedotin and R-CHP Chemotherapy - Rajiv M. Mallipudi; Lance Alquran; Vishnu A. Shenoy; Lori A. Leslie; John A. Conti (Case Reports in Oncological Medicine)
Introduction. The diagnosis of B-cell lymphoma, unclassifiable, with features intermediate between diffuse large B-cell lymphoma (DLBCL) and classical Hodgkin’s lymphoma (cHL), also referred to as grey zone lymphoma (GZL), is a challenging diagnosis. There are no standardized guidelines; however, evidence strongly suggests that DLBCL-based regimens are effective in the treatment of GZL. Brentuximab vedotin (BV) is an anti-CD30 antibody drug conjugate that has established efficacy in relapsed/refractory Hodgkin and some T-cell lymphomas. There is some evidence that BV has a positive response in non-Hodgkin lymphoma (NHL) with a wide range of CD30 expressions—including GZL. Case. We present a case of a patient initially diagnosed with cHL who underwent repeat biopsy which was revealed to be GZL. Based on PET scanning and immunohistochemical studies, she was classified as a stage IIIA CD20+/CD30+ GZL patient. Given her strong CD30 expression, she underwent 6 cycles of R-BV-CHP (rituximab, brentuximab vedotin, cyclophosphamide, doxorubicin, and prednisone) chemotherapy and achieved complete response (CR) both clinically and radiographically. Discussion. Given the rarity of GZL, this case illustrates the immense challenges in making the diagnosis, discusses the current treatment options, and suggests that BV may be a viable therapeutic candidate in the treatment of GZL.